2001
DOI: 10.1046/j.1365-2486.2001.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrated models of livestock systems for climate change studies. 1. Grazing systems

Abstract: The potential impact of climate change by the year 2050 on British grazing livestock systems is assessed through the use of simulation models of farming systems. The submodels, consisting of grass production, livestock feeding, livestock thermal balance, the thermal balance of naturally ventilated buildings and a stochastic weather generator, are described. These are integrated to form system models for sheep, beef calves and dairy cows. They are applied to scenarios representing eastern (dry) lowlands, wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…Ignoring practitioners' realities and attitudes, however, can mean missing important impacts as well as adaptation measures. Studies providing data on the role of adaptation to the climate change indicate that the economic impact tend to be neutral or even positive if adaptation is included (Parsons et al, 2001;Hossel, 2002;Fitzgerald et al, 2009), whereas the impact is negative when no adaptation is included (Leva et al, 1996;Mader et al, 2009;Moran et al, 2009;Walter and Lö pmeier, 2010). Similar results can be observed in cropping studies (Kaiser et al, 1993;Segerson and Dixon, 1999).…”
Section: The Economics Of Dairy Farming Under Climate Changementioning
confidence: 99%
“…Ignoring practitioners' realities and attitudes, however, can mean missing important impacts as well as adaptation measures. Studies providing data on the role of adaptation to the climate change indicate that the economic impact tend to be neutral or even positive if adaptation is included (Parsons et al, 2001;Hossel, 2002;Fitzgerald et al, 2009), whereas the impact is negative when no adaptation is included (Leva et al, 1996;Mader et al, 2009;Moran et al, 2009;Walter and Lö pmeier, 2010). Similar results can be observed in cropping studies (Kaiser et al, 1993;Segerson and Dixon, 1999).…”
Section: The Economics Of Dairy Farming Under Climate Changementioning
confidence: 99%
“…In Africa, impacts of droughts (1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999) have been shown to induce mortality rates of 20-60% of national herds (12). New models of animal energetics and nutrition (70) have shown that high temperatures put a ceiling on dairy milk yield from feed intake. In the tropics, this ceiling occurs between one-third and one-half of the potential of the modern (Friesians) cow breeds.…”
Section: Impacts On Weed and Insect Pests Diseases And Animal Produmentioning
confidence: 99%
“…Note that the smaller animal production adjustment could be due to the fact that we assumed zero impact of climate change on animal yields. This is based on the assumption that the direct effect of climate change on individual animals would be very small for the next fifty years (Parsons et al 2001). Price adjustments of agricultural commodities tend to reduce the impact of climate change on production.…”
mentioning
confidence: 99%